COMPOSITION AND VOLUMES OF GRANITOID COMPLEXES OF THE MIDDLE-PRYDNEPROVIE MEGABLOCK OF THE UKRAINIAN SHIELD - Kostenko, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
By the results of interpretation of the chemical and geochemical data by quantitative methods taking into account dates of the geokhronology partition of granitoids of Middle-Prydniprovie megablock of the Ukrainian Shield is carried out and certain the rocks composition of the selected granytoyd's complexes.